Spatial Distribution, Source Apportionment, and Pollution Assessment of Toxic Metals Around Agricultural Soils Based on APCS-MLR Receptor Modelling: A Case Study of the Northern Slope of Tianshan Mountains - Buasi Nueraihemaiti; Halidan Asaiduli; Abudugheni Abliz; Panqing Ye; Xianhe Liu (Land)
To investigate the contamination status and analyze the sources of soil toxic metal contamination on the northern slopes of the East Tianshan mountain industrial belt in Xinjiang, northwest China, this study measured the contents of six common toxic metals such as Zn, Cu, Cr, Pb, Hg and As in 82 surface soil (0–20 cm), and using the ground accumulation index, pollution load index, and improved weighted index assessed the contamination characteristics of the soil and using a semi-variance function and APCS-MLR model the identified the potential sources of contamination. The results indicate that the average concentrations of Pb, Hg, and As are significantly higher than the background values in Xinjiang. The average ranking of toxic metal content is as follows: Zn > Cr > Pb > Cu > Hg > as. A single-factor pollution index analysis shows that As and Pb pollution are severe, while Hg and Cu pollution are moderate. The improved weighted index shows that moderate lead pollution accounts for 6.1% and severe lead pollution accounts for 54.88%; 98.88% of arsenic is severely contaminated. The APCS-MLR model identified three main sources of heavy metals: Cu and Cr as industrial production sources, Pb and Zn as transportation and agricultural activity sources, and As, Cr, Cu, Hg, and Zn as natural and mixed pollution sources. This study provides a solid scientific basis for the prevention and control of toxic metal pollution in agricultural soils, thus ensuring food security and sustainable development in the region.